2016
DOI: 10.18632/oncotarget.12189
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HuR inhibition by the small molecule MS-444 on colorectal cancer cell tumorigenesis

Abstract: Colorectal cancer (CRC) is the third most common cancer and a leading cause of cancer-related mortality. Observed during CRC tumorigenesis is loss of post-transcriptional regulation of tumor-promoting genes such as COX-2, TNFα and VEGF. Overexpression of the RNA-binding protein HuR (ELAVL1) occurs during colon tumorigenesis and is abnormally present within the cytoplasm, where it post-transcriptionally regulates genes through its interaction with 3′UTR AU-rich elements (AREs). Here, we examine the therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 63 publications
1
86
0
Order By: Relevance
“…HuR function was perturbed using a small molecule inhibitor MS-444 that prevents HuR dimerization, a step critical for its stress- induced translocation to the cytoplasm (40, 41). Immunoblotting (Supp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HuR function was perturbed using a small molecule inhibitor MS-444 that prevents HuR dimerization, a step critical for its stress- induced translocation to the cytoplasm (40, 41). Immunoblotting (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that inhibition of the HuR/PARG axis enhances PARP-trapping on chromatin, and can be translated to improve PARPi efficacy in all PDAs, regardless of DNA repair status. In fact, we inhibited PARG expression using MS-444, a previously characterized tool for HuR inhibition (32, 41, 51). We consequently observed increased PARPi efficacy both in vitro and in vivo , independent of the cell line used (Fig 3C, 5A).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the best-characterized small molecule inhibitor of HuR is the chrysanthone-like compound MS-444 that inhibits HuR homodimerization and its cytoplasmic translocation (30,48). There have been promising pre-clinical studies that show MS-444 has potent affects in CRC mouse models (30) and other studies have demonstrated that MS-444 sensitizes PDA cells to oxaliplatin and 5-fluorouracil in relevant tumor microenvironment conditions, but issues with stability and bioavailability of MS-444 may hinder first human applications (17). Recently, there have been success in identifying other small molecules that disrupt the HuR-mRNA interactions, leading to impaired HuR function and premature decay of mRNAs that encode proteins related to tumor processes (37).…”
Section: Discussionmentioning
confidence: 99%
“…Parental HCT116 and HuR knockout clones 1 and 2 (2 × 10 6 cells) used between passages 14 – 23 were resuspended in PBS containing 50% Matrigel (Corning) and injected into the dorsal subcutaneous tissue. Tumor growth was assayed as described (28,30). …”
Section: Methodsmentioning
confidence: 99%
“…Given the extreme dosage sensitivity of Dyrk1a and its implication in numerous neurodevelopmental disorders, our finding that Dyrk1a protein levels are regulated in a Mena-dependent manner in axons raises the intriguing possibility that dysregulation of the Mena-RNP complex may contribute to such disorders. Additional mRNAs that are associated with Mena, like the validated targets β-catenin and elavl1 (HuR) are also implicated in multiple developmental processes and pathophysiological conditions (Alami et al, 2014; Blanco et al, 2016; Holland et al, 2013; Krumm et al, 2014; Li et al, 2017; Lu et al, 2014; O’Roak et al, 2012; Wang et al, 2016). Therefore, the Mena-RNP complex may represent a target for the development of novel therapeutic strategies for multiple disease pathologies.…”
Section: Discussionmentioning
confidence: 99%